Tinjauan Yuridis Terhadap Sengketa Penipuan Dalam Praktik Waralaba - PUTRI, IKA RACHMAWATI SUKARNO; I, URBANISASI (Jurnal Ilmiah Wahana Pendidikan, 2023)
This article discusses a legal analysis of fraudulent disputes that occur in franchise practices. The main focus of this analysis is to look at fraud disputes in franchise practices from the perspective of civil society capita selekta. This research was conducted by collecting data from relevant primary and secondary legal sources. In the context of franchising, fraud disputes occur when the franchisor knowingly commits fraud or provides false information to the franchisee with the aim of making a profit. This kind of fraud often involves errors in understanding the franchise contract, injustice in business practices, lack of communication and support from the franchisor, and non-compliance with operational standards